2019
DOI: 10.1021/acs.jpcc.9b03328
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bonding and Electronic Structure in CdS/GO and CdSSe/GO Multilayer Films

Abstract: The local atomic structure of multilayer films of graphene oxide, cadmium sulfide, and cadmium sulfide−selenide was analyzed by Xray absorption fine structure spectroscopy. The films were prepared by sequential electrophoretic deposition and successive ion layer adsorption and reaction onto F-doped SnO 2 substrates. The obtained films were characterized by scanning electron microscopy, energy dispersive spectroscopy, Raman spectroscopy, UV−vis spectroscopy, and step-potential photocurrent response. From the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In both images, regions with 'graphitic' arrangement within the GO layer right at the interface with the PbS QDs layer can be clearly seen. This is yet another evidence of the suggested reducing effect PbS QDs, and other semiconductor and oxide nanoparticles, have on GO, that was observed throughout this study, and that has been reported by other authors [49,50].…”
Section: Sem and Tem Morphological Studiessupporting
confidence: 90%
“…In both images, regions with 'graphitic' arrangement within the GO layer right at the interface with the PbS QDs layer can be clearly seen. This is yet another evidence of the suggested reducing effect PbS QDs, and other semiconductor and oxide nanoparticles, have on GO, that was observed throughout this study, and that has been reported by other authors [49,50].…”
Section: Sem and Tem Morphological Studiessupporting
confidence: 90%
“…The optical characterization shows a band gap difference from 3 cycles to 5, 7 and 10, the blue shift in band gap for 3 cycles multilayers is attributed to cubic zinc blende structure in CdS nanoparticles, after and Tauc plot are presented, is noticeable that with the increase of the number of cycles, increase the film thickness and reduces the optical transmission spectra from 80% a 3 cycles to almost 20% with 10 cycles, the absorption edge is blue shifted, which is seen in the difference in band gap from ~2.90 to ~2.15 eV, that is attributed to electronic disorder induced by CdS nanoparticles phase distribution and graphene oxide intercalation [1], [13]. Theoretical calculations are ongoing to predict the size of CdS nanoparticles based in the absorption coefficient, also Urbach tail will be deduced [14].…”
Section: Resultsmentioning
confidence: 93%
“…GO/CdS multilayers are being widely studied due to the excellent physicochemical properties of GO and CdS, since CdS is a semiconductor with a band gap of ~2.4 eV, high absorption coefficient (~10 4 cm -1 ) in the visible region, high electrochemical stability, good electron affinity and high photoconductive behaviour. GO, for its part, has extraordinary properties in thermal and electrical conductivity, in addition, it was proven that the set of GO/CdS obtained by EPD/SILAR produces a chemical bond between carbon or sulphur (C-S) [1]. This hybrid (organic/inorganic) systems are currently being studied as potential materials in optical, electronic, and photocatalytic applications, due to GO matrix can enhance the charge separation of the photogenerated carriers overcoming the high intrinsic recombination rate of CdS nanoparticles [2].…”
Section: Introductionmentioning
confidence: 99%
“…The development of more efficient solar and photoelectrochemical cells lead to hybrid materials based on cadmium chalcogenides such as CdS, CdSSe, and CdTe, in graphene oxide (GO) or reduced graphene oxide (rGO) matrix (Kagkoura et al, 2017). Hybrid CdS 1-x Se x /GO multilayers prepared by facile and low-cost methods present an intriguing optoelectronic behavior, such as the variation in the density of states measured by X-ray absorption near edge structure (XANES) and the formation of new interband states (IS) related to the Se/S-GO skeleton interaction (Colina-Ruiz et al, 2019). The materials present a high but damped photocurrent vs. potential response for CdS/GO and CdS 0.5 Se 0.5 -GO multilayers, which is attributed to the electronic structure modification of the multilayers due to the S-deficiency or Cdexcess depending on the x-value.…”
Section: Photovoltaic and Photoelectrochemical Cellsmentioning
confidence: 99%
“…The materials present a high but damped photocurrent vs. potential response for CdS/GO and CdS 0.5 Se 0.5 -GO multilayers, which is attributed to the electronic structure modification of the multilayers due to the S-deficiency or Cdexcess depending on the x-value. As shown in Figure 1B), the direct bond of nanoparticles and GO matrix benefits the interfacial charge transfer from the conduction band and IS to graphene sheets, promoting the electron-hole pairs separation and enhancing the photocurrent activity (Colina-Ruiz et al, 2019;Wei et al, 2019). Our current work on this topic includes the study of other systems such as ZnS 1-x Se x /GO and possible application to photoelectrochemical cells that will exploit quasi-static photocurrent under applied potential for sustained water splitting.…”
Section: Photovoltaic and Photoelectrochemical Cellsmentioning
confidence: 99%